2019
DOI: 10.3892/etm.2019.8197
|View full text |Cite
|
Sign up to set email alerts
|

Increase in liver γδ�T�cells with concurrent augmentation of IFN‑β production during the early stages of a mouse model of acute experimental hepatitis B virus infection

Abstract: The role of γδ T cells in acute hepatitis B virus (HBV) infection remains unclear. For the present study, a mouse model of acute HBV infection was constructed using hydrodynamic injection-based transfection of an HBV DNA plasmid (pHBV). Subsequent changes in the percentages of γδ T cells, expression of activation molecules (CD25 and CD69) and the production of the inflammatory cytokines interferon (IFN)-γ and tumor necrosis factor-α (TNF-α) by liver γδ T cells were investigated using fluorescence-activated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It shows that in chronic hepatitis B (CHB), Vδ2 T cells decrease in patients’ peripheral blood and relate to less IFN-γ production and cytotoxic activity 75 . In a mouse model of acute HBV infection, liver γδ T cells and IFN-β production increased during the early stages of HBV infection, but there were no much changes in peripheral γδ T cells 76 . And IFN-α can enhance the cytotoxic function of peripheral γδ T cells in CHB 77 .…”
Section: γδ T Cells and Other Infection After Allo-hsctmentioning
confidence: 90%
“…It shows that in chronic hepatitis B (CHB), Vδ2 T cells decrease in patients’ peripheral blood and relate to less IFN-γ production and cytotoxic activity 75 . In a mouse model of acute HBV infection, liver γδ T cells and IFN-β production increased during the early stages of HBV infection, but there were no much changes in peripheral γδ T cells 76 . And IFN-α can enhance the cytotoxic function of peripheral γδ T cells in CHB 77 .…”
Section: γδ T Cells and Other Infection After Allo-hsctmentioning
confidence: 90%
“…Few studies have addressed the role of γδ T cells and MAIT cells during acute infection. In mouse models of HBV infection, γδ T cells were found in increased numbers in the liver and actively producing IFN-γ during the first days of infection [ 118 ]. Furthermore, the transfer of hepatic CXCR3 + CXCR6 + γδ T cells from naïve mice to mice with acute HBV infection led to reduced disease and viral loads [ 119 ].…”
Section: Hepatic T Cell Subsets During Acute-resolving Viral Hepatitismentioning
confidence: 99%
“…28 Patients with acute hepatitis B infections have reduced circulating blood γδ T cells and increased hepatic γδ T cells compared with patients with CHB, which might be explained by the elevation of the liver chemokine, IP-10, and RANTES. 29 Furthermore, in an acute HBVinfected mouse model, Chang et al 30 showed that the proportion of hepatic γδ T cells is significantly increased and the immune reaction to increased expression of HBV markers in the liver is enhanced through the secretion of IFN-γ and IFN-β. The proportion of intrahepatic and circulating γδ T cells among CHB-infected patients is negatively correlated with disease severity.…”
Section: γδ T Cells and Experimental/acute Liver Failurementioning
confidence: 99%